The Concept of Royal Garden on Balinese Kingdom ( Period X – XX Centuries) ( Study on Environmental Archaeology) - I Nyoman Wardi (Bumi Lestari Journal of Environment)
Research is aimed to utillize archaeologicxal data sources ( artifact, isncription, manuscript) toinventory and study royal garden conception in Balinese kingdom period ( X – X Ceturies). It was carried outby research method. Firstly data was collected by literature study, observation, and interview. Then collecteddata analylized by descriptive qualitative techniqueResults of the research showed as follows. Royal garden establishment were affected by environmentaland cultural elements. Environmetal elements consist of physical and biological elements. Most importantphysical elements which very determined for garden establishment were water resouce, climate (24 0 C – 26 0C ), and topography ( 0 % - 3 %).Biological elements included vegetation (floweral and sacred trees such as menuh, angsana, bodhi,yellow coconut tree), and fauna include frogs, birds, fish,bumblebee and others.Meanwhile cultural elelementsrelated to social an cultural values, religious value, technology of hydrology, sicence of etnobotani ,planology,art , and social behavior.Function of the the royal garden were : (1) as a place to seek a quiet atmosphere, (2) a place forpurification and mediation, (3) as supplier of ritual equipments and conservative function, (4) as a suitableplace for study, (5) as a place to manage state policies, (6) for recreation and entertainment, (6) symbol ofpolitical stability and state prosperity.Royal garden conception was much affected by availablity of water resouce.There was a tendency thatthe garden which established was not just intended to honor a living king, but it also purposed to worshipking’s achestors and others divenes. The royal garden design is a inseparated design of capital kingdom’smasters plan. Since the royal garden was intergrated with a temple, so there was a tendency to choose sacredspace or sacred compass point ( east, north, or north-east) for gadern establishment. This concept pattern wasbased by cosmic conciousness to maitain balance and harmony between macrocosm (bhuwana agung) andmicrocosm (bhuwana alit or kingdom state) in order to reach peacefulness, properity and welfare life on earth.